Identifying probable post-traumatic stress disorder: applying supervised machine learning to data from a UK military cohort. (2nd January 2019) - Leightley, Daniel; Williamson, Victoria; Darby, John; Fear, Nicola T.
Abstract: Background: Early identification of probable post-traumatic stress disorder (PTSD) can lead to early intervention and treatment. Aims : This study aimed to evaluate supervised machine learning (ML) classifiers for the identification of probable PTSD in those who are serving, or have recently served in the United Kingdom (UK) Armed Forces. Methods: Supervised ML classification techniques were applied to a military cohort of 13, 690 serving and ex-serving UK Armed Forces personnel to identify probable PTSD based on self-reported service exposures and a range of validated self-report measures. Data were collected between 2004 and 2009. Results: The predictive performance of supervised ML classifiers to detect cases of probable PTSD were encouraging when compared to a validated measure, demonstrating a capability of supervised ML to detect the cases of probable PTSD. It was possible to identify which variables contributed to the performance, including alcohol misuse, gender and deployment status. A satisfactory sensitivity was obtained across a range of supervised ML classifiers, but sensitivity was low, indicating a potential for false negative diagnoses. Conclusions: Detection of probable PTSD based on self-reported measurement data is feasible, may greatly reduce the burden on public health and improve operational efficiencies by enabling early intervention, before manifestation of symptoms.